Effect of organic matter and Si liquid fertilizer on growth and yield of sugar cane - Djajadi Djajadi; Sulis Nur Hidayati; Roni Syaputra (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2016)
Sugarcane is known to absorb more Si than any other nutrient from the soil; therefore continuous cropping of the plant at the same soil would bring consequences of more Si and organic matter depletion. Silicon (Si) is considered as a beneficial nutrient for sugarcane production while organic matter is well known as soil amendment. Field study was carried out to know the effect of organic and Si liquid fertilizer on growth, Si and N uptake, and yield of cane variety of PSBM 901. The study field was located at Kempleng village, Purwoasri, East Java and the study was done from May 2013 up to September 2014. Split plot design with three replicates was employed to arrange treatments. Organic matter types (no organic matter, Crotalaria juncea and manure) were set as main plots while Si liquid fertilizer concentration (0, 15% Si and 30% S) were arranged as sub plots. C juncea was planted at 15 days before planting of sugar cane, and after 35 days the C juncea were chopped and mixed into the soil. Manure was added one week before sugar cane was planted. Si liquid fertilizer was sprayed to the whole part of sugar cane plant at 30 and 50 days after sugar cane was planted. All treatments received basal fertilizer of 800 kg ZA/ha, 200 kg SP 36/ha and 300 kg KCl/ha. Results showed that interaction between organic matter and Si liquid fertilizer significantly affected on Si and N absorption, length of stem, yield and rendement of sugar cane. Addition of manure and followed by spraying of 30% Si liquid fertilizer gave the highest value of S and N absorption (869 g SiO2/plant and 720 g N/plant), cane yield (155.74 tons/ha) and rendement (8.15%).